Open reduction for neglected traumatic hip dislocation in children and adolescents - Mahajan, Neeraj; Kumar, Amit; Baketh, Mohmmad Sikander; Ali, Tanveer (International Journal of Research in Medical Sciences, 2020)
Background: Neglected traumatic dislocation of the hip is extremely rare in children, and the preferred treatment remains unclear. In this study we studied the role of open reduction in neglected traumatic hip dislocation in children and adolescents as a modality of treatment. Methods: Eight patients with a neglected, traumatic dislocation of the hip received in the emergency department of GMC, Jammu were managed by open reduction. Types of dislocations, associated lesions, treatment methods, complications, and clinical and radiological outcomes were reviewed in the study. Results: All patients presented with limp and pain. Six patients had minimal difficulty in squatting while two had marked difficulty. Leg lengths were within 2 cm in 7 of 8 cases at follow-up, and only 1 patient had a discrepancy greater than 2 cm. Conclusions: Open reduction is a satisfactory treatment for neglected hip dislocation. It restores joint stability, range of motion and limb length.